The Use of Jute Sack as a Potential Material for Fashion Accessories in Ghana - OCRAN, AUGUSTINA (KNUST, 2026)
A Project Report Submitted to the School of Graduate Studies Kwame Nkrumah University of Science and Technology in Partial Fulfilment of the Requirements for the Award of the Degree of Master of Philosophy